The effect of the R.E.A.C.T strategy on emotional creativity among sixth-grade science students - Ahmed, Yasmine Ahmed Rasheed; Reda, Fatima Abdul Amir Abdul (Edelweiss Applied Science and Technology, 2025)
The current research aimed to identify the effect of the R.E.A.C.T strategy on emotional creativity among sixth-grade science students. The research sample consisted of 65 students, divided into 33 students for the experimental group and 32 for the control group. An experimental design with partial control was chosen for both groups, including a pre-test to implement the experiment, and the integrity of the experiment was verified. To achieve the research objectives, the researchers adopted Averill [1] emotional creativity scale, which consists of three areas: emotional readiness, emotional novelty, and emotional authenticity, with a total of 30 items with graded answers. After completing the experiment, the data were analyzed, and it was concluded that the experimental group, whose students studied according to the R.E.A.C.T strategy, outperformed the control group, whose students studied using traditional methods, in emotional creativity. It was recommended that specialized training courses be provided by the Directorate of Preparation and Training at the Ministry of Education for biology and science teachers, focusing on the effective use of the R.E.A.C.T strategy to enhance emotional creativity.